Physisorbed versus chemisorbed oxygen effect on thermoelectric properties of highly organized single walled carbon nanotube nanofilms. Issue 23 (2nd March 2017) - Yarali, Milad; Hao, Ji; Khodadadi, Mohammad; Brahmi, Hatem; Chen, Shuo; Hadjiev, Viktor G.; Jung, Yung Joon; Mavrokefalos, Anastassios
Abstract : The effect of physisorbed vs. chemisorbed oxygen on highly organized single walled carbon nanotube (SWCNT) ultrathin films is investigated by correlating the thermoelectric properties measured by a suspended micro-device to the SWCNT structure. Abstract : The effect of physisorbed vs. chemisorbed oxygen on highly organized single walled carbon nanotube (SWCNT) ultrathin films is investigated by correlating the thermoelectric properties measured by a suspended micro-device to the SWCNT structure characterized by Raman spectroscopy and transmission electron microscopy. The results show that SWCNTs with weakly bonded oxygen molecules on the surface were determined to be initially p-type with metallic behavior and after annealing in vacuum they transition to n-type with semiconducting behavior where the charge transport is dominated by a 2D Mott variable range hopping mechanism due to molecular desorption. The structural characterization reveals that there is no change in the structure of the SWCNT network, indicating that the source of the drastic change in electrical properties is due to the molecule interaction with the surface of the SWCNT. Even though there is a significant change in the electrical properties, the thermal conductivity remains unchanged. On the other hand, the oxidized SWCNT sample with stronger C–O bonds exhibits purely p-type metallic behavior that is insensitive to annealing conditions and shows lower thermal conductivity values because of the enhanced phonon scattering due to the absorbed oxygen molecules and residual poly-methyl-methacrylate (PMMA).